2014
DOI: 10.5194/tc-8-1699-2014
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the dynamics of Pine Island Glacier, West Antarctica, to climate forcing for the next 50 years

Abstract: Abstract. Pine Island Glacier, a major contributor to sea level rise in West Antarctica, has been undergoing significant changes over the last few decades. Here, we employ a three-dimensional, higher-order model to simulate its evolution over the next 50 yr in response to changes in its surface mass balance, the position of its calving front and oceaninduced ice shelf melting. Simulations show that the largest climatic impact on ice dynamics is the rate of ice shelf melting, which rapidly affects the glacier s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 44 publications
6
81
0
Order By: Relevance
“…However, this comparison remains qualitative as most of the models we compare use different setups that are certainly responsible for a part of the spread between models. Figure 4 presents the evolution of the cumulated contribution of PIG drainage basin to SLR for the period 2000-2050 according to the SeaRISE M3 experiment and according to Joughin et al (2010), Favier et al (2014) and Seroussi et al (2014). As mentioned above, estimations from SeaRISE range from a very limited retreat of the grounded line (e.g., Fig.…”
Section: Ensemble Analysis On Pigmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this comparison remains qualitative as most of the models we compare use different setups that are certainly responsible for a part of the spread between models. Figure 4 presents the evolution of the cumulated contribution of PIG drainage basin to SLR for the period 2000-2050 according to the SeaRISE M3 experiment and according to Joughin et al (2010), Favier et al (2014) and Seroussi et al (2014). As mentioned above, estimations from SeaRISE range from a very limited retreat of the grounded line (e.g., Fig.…”
Section: Ensemble Analysis On Pigmentioning
confidence: 99%
“…Pine Island Glacier (Joughin et al, 2010;Favier et al, 2014;Seroussi et al, 2014) and Thwaites Glacier (Joughin et al, 2014) in particular have shown considerable contemporary grounding line retreat and thinning . Joughin et al (2010) present a first comprehensive modeling of Pine Island Glacier (PIG) based on a SSA model and using assimilation methods for initialization.…”
Section: Pig Ensemblementioning
confidence: 99%
See 3 more Smart Citations